Development of Genome-Wide SNP Markers for Barley via Reference- Based RNA-Seq Analysis - Tanaka, Tsuyoshi; Ishikawa, Goro; Ogiso-Tanaka, Eri; Yanagisawa, Takashi; Sato, Kazuhiro (Frontiers in Plant Science, 2019)
Marker-assisted selection of crop plants requires DNA markers that can distinguish between the closely related strains often used in breeding. The availability of reference genome sequence facilitates the generation of markers, by elucidating the genomic positions of new markers as well as of their neighboring sequences. In 2017, a high quality genome sequence was released for the six-row barley (Hordeum vulgare) cultivar Morex. Here, we developed a de novo RNA-Seq-based genotyping procedure for barley strains used in Japanese breeding programs. Using RNA samples from the seedling shoot, seedling root, and immature flower spike, we mapped next-generation sequencing reads onto the transcribed regions, which correspond to ∼590 Mb of the whole ∼4.8-Gbp reference genome sequence. Using 150 samples from 108 strains, we detected 181,567 SNPs and 45,135 indels located in the 28,939 transcribed regions distributed throughout the Morex genome. We evaluated the quality of this polymorphism detection approach by analyzing 387 RNA-Seq-derived SNPs using amplicon sequencing. More than 85% of the RNA-Seq SNPs were validated using the highly redundant reads from the amplicon sequencing, although half of the indels and multiple-allele loci showed different polymorphisms between the platforms. These results demonstrated that our RNA-Seq-based de novo polymorphism detection system generates genome-wide markers, even in the closely related barley genotypes used in breeding programs.